International business negotiations: analysis of cultural dimensions and impact on negotiations - Peleckis, Kęstutis (IJRDO - Journal of Business Management, 2017)
Context of the negotiations at the international level is faced with the differences between various cultures: a long-term attitude towards communication, the power placement, the uncertainties avoiding, emotional differences between the negotiating parties and others. These and other differences in cross-cultural dimensions can influence the process of negotiations between the representatives of different cultures in the negotiations. There may happen in a variety of misunderstandings in negotiations and between the two parties of the same culture, while the process of preparing for the talks with different cultures require The article discusses cultural dimensions, their effect on negotiations. The analysis performed the global scientific literature, cultural dimensions and presented their comparison. There are investigated international business negotiation context and cognition aspects also. Paper includes suggestions for further research of international negotiations